Gender- and subgroup-specific sensitivity analysis of alcohol consumption and mortality in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study - Moissl-Blanke, Angela P.; Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; Dawczynski, Christine; Stojakovic, Tatjana; März, Winfried; Kleber, Marcus E.; Lorkowski, Stefan (Data in Brief, 2021)
Abstract: This Data in Brief article contains further sensitivity analysis data related to the article “Alcohol consumption and mortality: the Ludwigshafen Risk and Cardiovascular Health (LURIC) study” [1]. Alcohol consumption data of participants in LURIC was collected using a questionnaire. This data was used to calculate the amount of alcohol consumption in g ethanol per day by using standard volumes and standard vol-% in different beverages in Germany. The data shown here provide results from the LURIC study stratified by gender. Furthermore, the LURIC study results were reproduced using other classifications, which were stratified in different literature data. In addition, our analysis provides data of alcohol consumption for smokers and non-smokers in the LURIC study cohort separately. Keywords: Gender-specific alcohol consumption; Sensitivity analysis; Mortality; Cardiovascular diseases; Diabetes mellitus; Atherosclerosis